Analisis Hukum Keluarga Islam tentang Sebambangan Naeki pada Adat Ogan Studi di Desa Bunglai Kecamatan Kedaton Peninjauan Raya Kabupaten Ogan Komering Ulu - Siska Purnama Sari; Eko Hidayat; Kartika Kartika (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Sebambangan naeki is a unique tradition in which a girl actively goes to the home of her prospective husband, who is still unmarried, to ask to be married. If the man refuses, the girl will insist on not returning home until he marries her. This practice is often carried out by girls who have not yet reached the ideal age for marriage according to modern standards. In the context of Ogan customary law, the dowry, which is usually very high—namely 5 suku (units) of gold, 500 kilograms of dodol, and money amounting to 50 million rupiah—is adjusted to the financial capability of the man’s family. This research aims to describe the implementation process of sebambangan naeki in Ogan customary law and to analyze its compatibility with Islamic family law in the community of Bunglai Village. The research method used is descriptive-analytical qualitative research, with a field study approach and data collection from primary sources (observation, interviews) and secondary sources (fiqh books, journals, and legislation). The results of the study show that sebambangan naeki is carried out as a way to shorten the marriage process, mainly due to economic factors, the desire to accelerate marriage, lack of parental consent, or the presence of disgrace such as pregnancy outside of marriage. The process includes notification through a farewell letter, reporting to the village government, family deliberation (called nyuhok kesalahan), and administrative settlement. From the perspective of Islamic law, this tradition can be considered valid if it fulfills all the pillars and conditions of marriage, including the consent of both parties and the giving of a dowry. However, aspects of maturity (baligh) and public interest (maslahah) must be taken into consideration, especially because many of the participants are underage teenagers. From the perspective of Indonesian positive law, this practice often conflicts with Law Number 16 of 2019 on Marriage, which sets the minimum age at 19, so underage couples require a dispensation from the Religious Court. The conclusion of this study is that sebambangan naeki is a complex customary solution, situated at the crossroads between the recognition of customary and religious norms on the one hand, and state legal provisions on the other. Therefore, synergy is needed among traditional leaders, the government, and religious institutions to provide comprehensive understanding to the community, so that positive customary values can be preserved without neglecting legal protection, especially for children and women.